Harlequin color change in two preterm newborns. Issue 1 (8th November 2013) - Dang, Dan; Zhou, Wenli; Liu, Ying; Wu, Hui
Abstract Harlequin color change is a benign transient skin change usually seen in the neonatal period with unknown etiology. It has been rarely reported in preterm infants. Herein, we report two cases of harlequin color change developed in premature infants without any adverse consequences. During the event, one infant was receiving antibiotic treatment for an Escherichia coli bacteremia in addition to routine supportive care and the other one was in a very stable condition. Both preterm infants were also diagnosed to have a patent ductus arteriosus. As a benign transient skin change, harlequin color change should be recognized properly to avoid unnecessary treatment.